THE INFLUENCE OF ACHIEVEMENT MOTIVATION AND LEADERSHIP TO THE WORK OF EMPLOYEES IN THE TOWN OF TENGGARONG KUTAI KARTANEGARA REGENCY OPPOSITE - Wijayanti, Elly (PREDIKSI, 2014)
The Influence Of Leadership On The Work Achievement Employees In District Of Tenggarong Kutai Kartanegara Regency Opposite.This research aims to find data and information on the implementation of human resources empowerment in improving employee performance and know what are the obstacles in the implementation of human resources empowerment in improving employee performance as well as find out about problem-solving efforts done to overcome the obstacles of implementation of human resources empowerment in improving the performance of employees at an Office in the Town of Tenggarong Kutai Kartanegara Regency of .The result of the research is that; Based Upon the results of data analysis, whether in the form of deskripsidata and hypothesis testing, then partially contained significant positive influence Pimimpinan of employee accomplishments Office of the Town of Tenggarong Kutai Kartanegara Regency Opposite. Halinidapatdilihatdari results of the counting of the data which thitung (X 1 = 1,716) > ttabel. (1,703).With a high motivation work achievement expected of the employees were also higher. In addition, the data is also reinforced by the description of Mr. h. Totok Sunarto, SP. MM, as the head of Tenggarong Kutai Kartanegara Regency, Opposite that employees who work the Office has a high achievement due to the attitude of the democratic leadership is applied by the leadership in this regard is the Head, so that the achievements of the work of his officers were also on the rise. Each has something to do with the interests of employees, the Office (direction through Sekcam) always promotes employees. So according to him there is a transparent siantara Office (Chairman) and its employees. the employees, so that there is a tendency in low motivation then his achievements were also low.As has been pointed out in the discussion above, that motivation is one of the important factors in an effort to increase the level of employment an employee achievement. However, apart from the factor of motivation are not equally important is good leadership factor, which is applied by a leader in order to affect the soldiers, and in this study proved that variable leadership turned out to be a significant positive effect on the work achievement of Tenggarong Subdistrict Office employees across the District kukar. It can be proved by the results of the calculations through the help of the program SPSS for Windows ver. 17, conducted by the researchers, in a study partially variable of leadership can be shown with the value koefisienthitung lebihkecildarittable yaituX2 = 0.546 > 1,703. So from the above calculation can be inferred that, variable partial leadership potential negative influence on the work achievement of Tenggarong Subdistrict Office clerk in Opposite Kukar.As already outlined in the previous discussion that a simultaneous leadership variable has a significant positive effect on employee work performance, it can be seen from the test by using a Test F IE testing all together against the leadership of the variables work achievement a clerk in an Office opposite the Tenggarong subdistrict of the Kutai Kartanegara Regency, which suggests that the results of the calculation of the value of the Fhitung hypothesis amounted to 8.744 .40 sedangkannilaiFtabel3. Pada pengujian ini H0 rejected because (8.744 > 3.40) of the results shows that the variables of motivation and leadership when tested simultaneously or terdapatpengaruh very closely together towards achievement of work clerk in kantorKecamatanTenggarong opposite the District kukar.In the blurb has been previously explained that the leadership factor is a factor which is very vital in order to increase the quality of the work and accomplishments of its employees. And this is where the role of a leader in giving good direction and influence to his very necessary, because the pattern of good leadership will greatly affect the results that will be obtained by his subordinates. Here in every Stride a good leader is always striving to provide the service to his subordinates and always favors the interests of the Member or employee, other than that a good leader in the leadership, so it will always hold fast to the principles of truth and justice in order to achieve the common good.So it is clear already that in addition to motivation factors are needed for the efforts of the employees, work achievement improvement factor applied by the leadership of a Chief was also very influential and very big role against the efforts to improve the quality and achievements of the work of the employees.